2015
DOI: 10.1111/famp.12198
|View full text |Cite
|
Sign up to set email alerts
|

Finer Distinctions: Variability in Satisfied Older Couples’ Problem‐Solving Behaviors

Abstract: This study utilized observational and self-report data from 64 maritally satisfied and stable older couples to explore if there were meaningful differences in how couples approached marital disagreements. Using a typology approach to classify couples based on their behaviors in a 15-minute problem-solving interaction, findings revealed four types of couples: (1) problem solvers (characterized by both spouses' higher problem-solving skills and warmth), (2) supporters (characterized by both spouses' notable warm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 60 publications
3
22
0
Order By: Relevance
“…Consistent with this suggestion and with previous research Hawkins & Erickson, 2015;Quirk et al, 2014), in the present study distressed couples evidenced the greatest treatment gains, whereas non-distressed couples reported small effects. However, although the effects for non-distressed couples overall were small, even small reductions in negativity can have substantial long-term impacts on couple functioning (Rauer, Williams, & Jensen, 2015).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Consistent with this suggestion and with previous research Hawkins & Erickson, 2015;Quirk et al, 2014), in the present study distressed couples evidenced the greatest treatment gains, whereas non-distressed couples reported small effects. However, although the effects for non-distressed couples overall were small, even small reductions in negativity can have substantial long-term impacts on couple functioning (Rauer, Williams, & Jensen, 2015).…”
Section: Discussionmentioning
confidence: 82%
“…Thus, specifically targeting moderately distressed couples in future research may aid in improving overall effect sizes as these couples might be more motivated to apply the skills learned and have greater opportunity to evince change in relationship satisfaction. However, although the effects for non-distressed couples overall were small, even small reductions in negativity can have substantial long-term impacts on couple functioning (Rauer, Williams, & Jensen, 2015). However, although the effects for non-distressed couples overall were small, even small reductions in negativity can have substantial long-term impacts on couple functioning (Rauer, Williams, & Jensen, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…People can have simultaneously positive and negative feelings for one another (Fingerman, Hay, & Birditt, 2004; Rauer, Williams, & Jensen, 2015; Rauer & Volling, 2013). Negative aspects of relationships also tend to be more highly associated with marital longevity as well as with psychological and physical well-being than do the positive aspects of relationships (Karney & Bradbury, 1995; Kurdek, 1995; Orbuch, Veroff, Hassan, & Horrocks, 2002; Umberson, Williams, Powers, Liu, & Needham, 2006).…”
Section: Marital Tensionmentioning
confidence: 99%
“…Behavioral theory suggests that spouses may have unintentionally rewarded negative behaviors throughout the marriage, resulting in continued, albeit moderate, displays of negativity that may erode spouses' marital satisfaction (Patterson & Reid, 1970). Although previous work has suggested that younger husbands' negativity may not necessarily be harmful to their wives' marital satisfaction (Huston & Vangelisti, 1991), older spouses may be particularly sensitive to husbands' negativity given their focus on maximizing positive and rewarding interactions during later life (Carstensen, 1992;Rauer, Williams, & Jensen, 2016).…”
Section: The Powerful Role Of Husbands' Negative Affect In Marital Samentioning
confidence: 99%